2014
DOI: 10.1103/revmodphys.86.153
|View full text |Cite
|
Sign up to set email alerts
|

Quantum simulation

Abstract: Simulating quantum mechanics is known to be a difficult computational problem, especially when dealing with large systems. However, this difficulty may be overcome by using some controllable quantum system to study another less controllable or accessible quantum system, i.e., quantum simulation. Quantum simulation promises to have applications in the study of many problems in, e.g., condensed-matter physics, high-energy physics, atomic physics, quantum chemistry and cosmology. Quantum simulation could be imple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
2,220
1
20

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 2,616 publications
(2,315 citation statements)
references
References 365 publications
(489 reference statements)
13
2,220
1
20
Order By: Relevance
“…Some of these results have already appeared in the quantum computation literature in the context of in depth studies of state preparation [24,25]. A general review of quantum simulation [26,27] and one on quantum computation for chemistry [28] cover these topics in more depth. A collection covering several aspects of quantum information and chemistry recently appeared [29].…”
Section: Introductionmentioning
confidence: 99%
“…Some of these results have already appeared in the quantum computation literature in the context of in depth studies of state preparation [24,25]. A general review of quantum simulation [26,27] and one on quantum computation for chemistry [28] cover these topics in more depth. A collection covering several aspects of quantum information and chemistry recently appeared [29].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly significant is the exponential speed up achieved for the prime factorization of large numbers [3], a problem for which no efficient classical algorithm is currently known. Another attractive area for quantum computers is quantum simulation [4][5][6][7][8][9] where it has recently been shown that the dynamics of chemical reactions [10] as well as molecular electronic structure [11] are attractive applications for quantum devices. For all these instances, the realization of a quantum computer would challenge the Extended Church-Turing thesis (ECT), which claims that a Turing machine can efficiently simulate any physically realizable system, and even disprove it if prime factorization was finally demonstrated to be not efficiently solvable on classical machines.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary motivations for the development of quantum computation is the possibility of efficiently simulating quantum systems [1]- [3], as suggested in Feynman's seminal paper on the topic [4]. The natural first step towards this vision is the simulation of closed quantum systems, undergoing Hamiltonian generated unitary evolution, and over the past two decades consistent progress has been made in this field.…”
Section: Introductionmentioning
confidence: 99%